Pelatihan Penanganan Korban Gigitan dan Sengatan Hewan Untuk Meningkatkan Pengetahuan Siswa/I Kelas 11 Madrasah Aliyah Miftahul Ulum Anggana - Viana; Milkhatun; Siti Khoiroh Muflihatin; Zulmah Astuti; Alfi Ari Fakhrur Rizal (Open Edutech Indonesia, 2024)
Animal bites and stings are a significant public health issue in Indonesia, a country with high biodiversity. Students are one of the most vulnerable groups to animal bites and stings, especially in school environments that are often adjacent to forests or plantations. This study aimed to evaluate the effect of animal bite and sting first aid training on the knowledge of 11th-grade students at Madrasah Aliyah Miftahul Ulum Anggana. A pre-experimental design with a one-group pretest-posttest design was used. A total of 35 students participated in the study. The results showed that the mean knowledge score of the respondents before training was 18.47, and after training increased to 19.71. This increase in knowledge was statistically significant (p < 0.05). Based on the results of this study, it can be concluded that animal bite and sting first aid training is effective in improving the knowledge of 11th-grade students at Madrasah Aliyah Miftahul Ulum Anggana.